Vitamin D levels and bone mineral density: a prospective cross-sectional analysis of young orthopedic trauma patients at a rural United States trauma center - Michael Booth; Kenneth Sabacinski; Colleen Watkins; Erin Butcho; Emilie Kramer; Lukas Meadows; Michelle A. Bramer (Journal of Trauma and Injury)
Purpose The goal of this cross-sectional study was to investigate the prevalence of vitamin D deficiency in young orthopedic trauma patients and its impact on bone mineral density (BMD) measured through computed tomography imaging of the lumbar spine. Methods Conducted at a level I trauma center, this prospective cross-sectional analysis included 100 patients aged 18 to 50 years with non-fragility fractures. Vitamin D levels and Hounsfield units of the lumbar spine were recorded from computed tomography scans. Exclusion criteria included fragility fractures, lumbar surgery history, or lumbar bony/metastatic lesions. The correlation between vitamin D levels and BMD was assessed; vitamin D deficiency was defined as below 30 ng/mL. Results Among the participants, 75% were vitamin D–deficient, with an average vitamin D level of 25.0 ng/mL. No patients had osteoporosis based on Hounsfield units; however, 5% of patients were in the osteopenic range. In patients with normal vitamin D levels, there was an inverse correlation between vitamin D levels and BMD measured by Hounsfield units (P=0.025). Higher lumbar spine Hounsfield unit measurements correlated with lower vitamin D levels in this nondeficient population. Conclusions This study highlights a high prevalence of vitamin D deficiency in young orthopedic trauma patients, and it suggests a potential inverse relationship with BMD in patients with vitamin D levels >30 ng/mL. The absence of osteoporosis in our population raises questions about the influence of vitamin D on BMD in this young trauma patient demographic. Future research should explore the impact of vitamin D replacement on fracture union and investigate the interaction between vitamin D levels and bone health in the younger orthopedic trauma population.